2012
DOI: 10.1089/aid.2011.0248
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Lymphotropic Virus Type 1 Prevalence in Northeastern Iran, Sabzevar: An Epidemiologic-Based Study and Phylogenetic Analysis

Abstract: Human T-lymphotropic virus type 1 (HTLV-I) is an important global health problem in the world mainly in the endemic areas of HTLV-I infection. It was previously reported that Mashhad, in northeastern Iran, is a new endemic region of HTLV-I. The aim of this study was to examine the prevalence and phylogenetic analysis of HTLV-I in Sabzevar, located in the southeast of Mashhad. In this cross-sectional study 1445 individuals were selected by multistage cluster sampling. Serum samples were screened for anti-HTLV-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…According to the type of studies and of tested populations, HTLV-1 prevalence is estimated to range from 0.77 to 3% in adults (Safai et al, 1996; Abbaszadegan et al, 2003; Rafatpanah et al, 2011). A more recent study indicates an HTLV-1 prevalence of 1.66% in adults from the city of Sabzevar located in the Southeast of Mashad and confirmed that HTLV-1 is highly endemic in this region (Azarpazhooh et al, 2012). Furthermore, relatively large series of ATL as well as TSP/HAM cases originating from the Mashad region are reported in Iran (Sidi et al, 1990; Kchour et al, 2009) but also in Iranian immigrants living in European countries, the United States, or Israël (Sidi et al, 1990; Gabarre et al, 1993; Miller et al, 1998).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 72%
“…According to the type of studies and of tested populations, HTLV-1 prevalence is estimated to range from 0.77 to 3% in adults (Safai et al, 1996; Abbaszadegan et al, 2003; Rafatpanah et al, 2011). A more recent study indicates an HTLV-1 prevalence of 1.66% in adults from the city of Sabzevar located in the Southeast of Mashad and confirmed that HTLV-1 is highly endemic in this region (Azarpazhooh et al, 2012). Furthermore, relatively large series of ATL as well as TSP/HAM cases originating from the Mashad region are reported in Iran (Sidi et al, 1990; Kchour et al, 2009) but also in Iranian immigrants living in European countries, the United States, or Israël (Sidi et al, 1990; Gabarre et al, 1993; Miller et al, 1998).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 72%
“…Northeast province of Iran (Mashhad, Sabzevar, and Neyshabour) and Urmia are known to be an endemic area for HTLV-1, where the prevalence of HTLV-1 infection was reported to be 0.34–0.77% in blood donors (Abbaszadegan et al, 2003; Khameneh et al, 2008), 1.7–12% in cross-sectional studies (Meytes et al, 1990; Safai et al, 1996; Hedayati-Moghaddam et al, 2011; Azarpazhooh et al, 2012), and 2–3% in community-based population (Rafatpanah et al, 2011). …”
Section: Incidence and Prevalencementioning
confidence: 99%
“…In Iran, HTLV-1 is endemic at least in 2 provinces, including Khorasan Razavi and Northern Khorasan. However, HTLV-1-associated disorders have been reported from other provinces such as Golestan, Alborz, and East Azarbayejan [3,[6][7][8]. About 2-5 % of infected people develop adult T-cell leukemia/lymphoma (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) [9,10].…”
Section: Introductionmentioning
confidence: 99%